Considering the Case for Diversity in Natural Resources. (15th July 2020) - Batavia, Chelsea; Penaluna, Brooke E; Lemberger, Thea Rose; Nelson, Michael Paul
Abstract: Although there is widespread support for diversity in natural resources, diversity is valued for different reasons. It is important to understand and critically examine these reasons, to ensure diversity efforts express clear thinking and appropriate motivations. We compiled recent (2000–2019) diversity literature in fisheries, forestry, range, and wildlife, and used a qualitative coding procedure to identify reasons articulated in support of diversity. We developed a subset of these reasons into formal arguments to assess their underlying beliefs and assumptions. Our analysis reveals a high frequency of instrumental arguments emphasizing the benefits of diversity for natural resources. Drawing on the large body of interdisciplinary diversity scholarship outside natural resources, we discuss the challenges and potential risks of predicating the case for diversity largely on instrumental arguments. We encourage natural resources communities to expand the diversity discourse by engaging with themes developed in interdisciplinary diversity literatures, including equity, social justice, and intersectionality.